Improbable magic for cynical witches eaudiobook - Scelsa, Kate (Storytide, 2022)
A witchy, atmospheric lesbian contemporary romance set in Salem—from the acclaimed author of Fans of the Impossible Life. Perfect for fans of Nina LaCour and Becky Albertalli. Seventeen-year-old Eleanor is the last person in Salem to believe in witchcraft—or to think that her life could be transformed by mysterious forces. After losing her best friend and first love, Chloe, Eleanor has spent the past year in a haze, vowing to stay away from anything resembling romance. But when a handwritten guide to tarot arrives in the mail at the witchy souvenir store where Eleanor works, it seems to bring with it the message that magic is about to enter her life. Cynical Eleanor is quick to dismiss this promise, until real-life witch Pix shows up with an unusual invitation. Inspired by the magic and mystery of the tarot, Eleanor decides to open herself up to Pix and her coven of witches, and even to the possibility of a new romance. But Eleanor's complicated history continues to haunt her. She will have to reckon with the old ghosts that threaten to destroy everything, even her chance at new love. Improbable Magic for Cynical Witches is an atmospheric and romantic coming-of-age about learning to make peace with the past in order to accept the beauty of the present.